2009
DOI: 10.1161/circep.109.848978
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Efficacy and Safety of Electroanatomic Circumferential Pulmonary Vein Ablation Supplemented by Ablation of Complex Fractionated Atrial Electrograms Versus Potential-Guided Pulmonary Vein Antrum Isolation Guided by Intracardiac Ultrasound

Abstract: Background-The study was conducted to compare relative safety and efficacy of pulmonary vein antrum isolation (PVAI) using intracardiac echocardiographic guidance and circumferential pulmonary vein ablation (CPVA) for atrial fibrillation (AF) using radiofrequency energy. Methods and Results-Sixty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 32 publications
(29 reference statements)
3
51
0
2
Order By: Relevance
“…After a mean follow-up of 24 ± 12 months, antral PVI was more likely to achieve control of atrial tachyarrhythmias off antiarrhythmic drugs (57% vs. 27%, P = 0.02). 16 Similar results were shown by Karch et al in a study that randomized 100 patients to circumferential PV ablation or segmental PVI guided by a circular mapping catheter.…”
Section: Techniques and Outcomes Of Pvisupporting
confidence: 78%
See 2 more Smart Citations
“…After a mean follow-up of 24 ± 12 months, antral PVI was more likely to achieve control of atrial tachyarrhythmias off antiarrhythmic drugs (57% vs. 27%, P = 0.02). 16 Similar results were shown by Karch et al in a study that randomized 100 patients to circumferential PV ablation or segmental PVI guided by a circular mapping catheter.…”
Section: Techniques and Outcomes Of Pvisupporting
confidence: 78%
“…6,[8][9][10] Wide antral PV isolation guided by recordings from a circular mapping catheter has been demonstrated superior to other ablation techniques in studies of direct comparison. 6,16 Circumferential PV ablation guided by nonfluoroscopic electroanatomic mapping systems, without confirmation of electrical isolation with a circular mapping catheter, has been demonstrated ineffective in achieving long-term arrhythmia control. 7,16 In a randomized comparison between CARTO ® -guided circumferential PV ablation (Biosense Webster, Inc., Diamond Bar, CA) and PV antrum isolation with ICE and a circular mapping catheter, 16 Khaykin et al studied 60 patients with drug-refractory AF with the end point of long-term procedural success defined as the absence of atrial tachyarrhythmias off antiarrhythmic drugs.…”
Section: Techniques and Outcomes Of Pvimentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Previous studies have reported significantly better outcome with PVAI guided by circular mapping catheter over 3D mapping-guided circumferential PV isolation. 28,29 Also, in a meta-analysis by Proietti et al, wideantral approach encompassing the part of the posterior wall in between the PVs was observed to be more effective than ostial PV isolation in achieving freedom from arrhythmia. 30 For Shah et al, 14 the recurrence rate at 1, 2, 3, 4, and 5 years of follow-up were 8.7%, 5.8%, 8.8%, 13%, and 25.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have demonstrated superior results for restoration of normal sinus rhythm with catheter ablation compared with antiarrhythmic drug therapy, despite some patients requiring multiple ablation procedures (84)(85)(86)(87)(88). When catheter ablation is used in combination with antiarrhythmic drug therapy, the success rate of achieving normal sinus rhythm was 71% [95% confidence interval (CI), 65-77%], which is superior to antiarrhythmic drug therapy alone at 57% (95% CI, 50-64%) (88).…”
Section: Discussionmentioning
confidence: 99%